2016
DOI: 10.1016/j.stem.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

LIN28 Regulates Stem Cell Metabolism and Conversion to Primed Pluripotency

Abstract: The RNA-binding proteins LIN28A and LIN28B play critical roles in embryonic development, tumorigenesis, and pluripotency, but their exact functions are poorly understood. Here, we show that, like LIN28A, LIN28B can function effectively with NANOG, OCT4, and SOX2 in reprogramming to pluripotency and that reactivation of both endogenous LIN28A and LIN28B loci are required for maximal reprogramming efficiency. In human fibroblasts, LIN28B is activated early during reprogramming, while LIN28A is activated later du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
264
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 291 publications
(294 citation statements)
references
References 51 publications
29
264
0
1
Order By: Relevance
“…glucose metabolism Zhang et al, 2016). Lin28a mRNA is reported to be expressed throughout the embryo at E8.5, but gradually becomes restricted to the posterior part of embryos as development proceeds (Balzer et al, 2010), resembling the dynamic expression pattern of Aldoa during CB (Fig.…”
Section: Lin28a As a Possible Intrinsic Timing Determinant Of Glucosementioning
confidence: 76%
“…glucose metabolism Zhang et al, 2016). Lin28a mRNA is reported to be expressed throughout the embryo at E8.5, but gradually becomes restricted to the posterior part of embryos as development proceeds (Balzer et al, 2010), resembling the dynamic expression pattern of Aldoa during CB (Fig.…”
Section: Lin28a As a Possible Intrinsic Timing Determinant Of Glucosementioning
confidence: 76%
“…Although the transcriptional regulatory network safeguarding the naive/primed state of pluripotency has been studied extensively, the role of posttranscriptional control mechanisms, particularly translational control, remained largely unexplored. The importance of posttranscriptional regulatory processes has been highlighted recently by the identification of the RNA-binding proteins Pum1 and Lin28 as regulators of naive/primed pluripotency (60,61). Detailed analysis of mRNA translation therefore should provide valuable information about the role of translational control in these pluripotent states.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated that cellular metabolism also plays an essential role in regulation of pluripotency, specifically through modulation of the epigenetic landscape (Zhou et al, 2012;Sperber et al, 2015;Zhang et al, 2016). In primed human PSCs, metabolism typically proceeds via the glycolytic pathway, which rapidly switches to oxidative phosphorylation upon differentiation (Zhou et al, 2012;Moussaieff et al, 2015).…”
Section: The Function Of Pi3k/akt/mtor In Regulating Glycolytic Metabmentioning
confidence: 99%